Pseudorabies virus glyprotein E gene: sequence analysis and relationship to other homologous genes - Allaudin, Zeenathul Nazariah; Mohd Lila, Mohd Azmi; Abdul Rahman, Sheikh Omar; Ideris, Aini; Bahaman, Abdul Rani; Mutalib, Abdul Rahim (Veterinary Association Malaysia, 2007)
The glycoprotein E (gE) gene is a virulence-associated gene of pseudorabies virus (PrV). This paper reports the first documented gE sequence analysis of a locally derived PrV. A comparative sequence analysis with other herpesviral gE homologues was also performed to give an insight on where it stands among the pool of genes. The gE gene of TK gE PrV features a typical type 1 membrane protein which starts with the initiator methionine and followed directly with a 27-amino-acids signal sequence. Basically the gene could be divided into three distinct functional domains: a 429-amino-acids ectodomain, a 26-amino-acid hydrophobic transmembrane domain and a 123-amino-acid, highly charged cytoplasmic domain. A high degree of gE gene conservation was shared between TK gE+ PrV and other PrV strains. Only 23 to 31% homology was found when compared among the gE proteins of alphaherpesvirus from diverse animals. Despite the low overall level of identity, considerable similarity of cystein rich regions was observed among gE genes, indicating some important sequences for the structure of these glyproteins. Although, the gE of PrV strains have closely conserved predicted N-Linked glycosylation sites, they have no counterparts in the homologous proteins of other alphaherpesviruses. Comparison of amino acid sequences with gE homologs indicated a greater diversity of sequences in the N- terminal region of the protein. It also highlighted several features of the gE protein conserved throughout the herpesvirus family which is also shared by TK gE+ PrV. Characterisation of the local Prv gE at molecular level may facilitate the construction of recombinant or chimeric PrV as vehicles for the delivery of vaccine antigens to the host.